2015
DOI: 10.1021/acsami.5b01706
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Hemin in Metal–Organic Frameworks for Catalyzing the Chemiluminescence Reaction of the H2O2–Luminol System and Detecting Glucose in the Neutral Condition

Abstract: Novel metal-organic frameworks (MOFs) based solid catalysts have been synthesized by encapsulating Hemin into the HKUST-1 MOF materials. These have been first applied in the chemiluminescence field with outstanding performance. The functionalized MOFs not only maintain an excellent catalytic activity inheriting from Hemin but also can be cyclically utilized as solid mimic peroxidases in the neutral condition. The synthesized Hemin@HKUST-1 composites have been used to develop practical sensors for H2O2 and gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(87 citation statements)
references
References 55 publications
1
86
0
Order By: Relevance
“…That is, the proton interchange was, by far, significant in Hm-Den mixture with respect to that revealed by Hm-Dim one. The major structural differences between melamines Dim and Den consisted mainly on their size (Scheme 2) and global shape, planar against vaulted, respectively; at this stage of our knowledge, we hypothesized a partial encapsulation of planar Hm (an already published [31][32][33][34] aptitude of this metaloporphyrine) by a multi-branched structure [31] such as Den, creating a new potential metal-organic framework (MOF) [32][33][34].…”
Section: Ft-ir Analysismentioning
confidence: 95%
“…That is, the proton interchange was, by far, significant in Hm-Den mixture with respect to that revealed by Hm-Dim one. The major structural differences between melamines Dim and Den consisted mainly on their size (Scheme 2) and global shape, planar against vaulted, respectively; at this stage of our knowledge, we hypothesized a partial encapsulation of planar Hm (an already published [31][32][33][34] aptitude of this metaloporphyrine) by a multi-branched structure [31] such as Den, creating a new potential metal-organic framework (MOF) [32][33][34].…”
Section: Ft-ir Analysismentioning
confidence: 95%
“…colorimetric biosensing. However, employment of MOFs as catalyst in CL analysis is rare [24][25][26]. For example, the group of Chen [24] found that Cu-BTC (HKUST-1) could be used as an effective catalyst to significantly enhance the CL emission of a luminol-H 2 O 2 system in basic medium.…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, a sensitive and selective CL method for CySH was proposed and successfully used for the detection of CySH in human serum samples. By encapsulating Heme into HKUST-1, Chi's group synthesized Hemin@HKUST-1 composite [26]. It was found that the Hemin@HKUST-1 composite displayed excellent catalytic activities toward the luminol-H 2 O 2 CL system both in alkaline and neutral media.…”
Section: Introductionmentioning
confidence: 99%
“…2D). The detection limit was calculated to be 0.1 μM (3σ rule), which is two orders of magnitude lower than other GNRs-based glucose sensors (Liu et al, 2013;Saa et al, 2014) and is almost the lowest among nanoparticle-based glucose sensors (Table S1, Supplementary Information) (Bi et al, 2015;Bo et al, 2013;Jiang et al, 2010;Kong et al, 2014;Luo et al, 2015;Radhakumary and Sreenivasan, 2011;Shen and Xia, 2014;Shiang et al, 2009;Su et al, 2012Su et al, , 2015bXia et al, 2013;Yi et al, 2013;Zayats et al, 2005;Zhao et al, 2015;Zheng et al, 2015). In addition, the small error bar of the data indicates the method has very high stability (Fig.…”
Section: Z Zhang Et Almentioning
confidence: 92%